2023
DOI: 10.1177/23197145231167707
|View full text |Cite
|
Sign up to set email alerts
|

The Divergence Effects of Knowledge Transfer in the Family Business: Evidence from Nanchang

Abstract: Because it affects the next generation, knowledge transfer is a crucial resource for succession in a family-owned business. This paper examines how knowledge transfer impacts family businesses in Nanchang, Jiangxi Province, China. Data collection is done via semi-structured interviews, and data manipulation is done using data categorization and contextualization techniques. The findings show that: (i) the effect of knowledge transfers through the founder and beyond the family business results in a large amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…This desire to preserve the business for future generations and ensure family continuity leads family members to manage their capital effectively (Lim et al, 2010) and invest in research and development (R&D) for the long-term (Craig & Dibrell, 2006). This is linked to the effort to pass on knowledge and experience across all levels of the company (Bell & Pham, 2020;Huang et al, 2023).…”
Section: Characteristics Of Family Businessesmentioning
confidence: 99%
“…This desire to preserve the business for future generations and ensure family continuity leads family members to manage their capital effectively (Lim et al, 2010) and invest in research and development (R&D) for the long-term (Craig & Dibrell, 2006). This is linked to the effort to pass on knowledge and experience across all levels of the company (Bell & Pham, 2020;Huang et al, 2023).…”
Section: Characteristics Of Family Businessesmentioning
confidence: 99%
“…In CFBs, the second generation of successors made the company's business more diversified and showed good performance (Weng et al, 2019), and they were more willing to spend on audits (Weng et al, 2023). Nevertheless, the proportion of male successors affected and restricted professional management (Shi et al, 2022) Huang et al (2023) found that the most common way for successors to inherit knowledge from founders was to innovate within the firm. Huang and Bao (2022) explored another angle, arguing that the successor's family and work were often independent of each other, which updated the life attitude of the older generation.…”
Section: Changes By Successorsmentioning
confidence: 99%
“…Knowledge transfer includes the transfer of tacit knowledge and explicit knowledge and is an important resource for inheritance. According to the research results of semi-structured interviews by Huang et al (2023), a large amount of tacit knowledge was formed in the founder's business process, such as skills, social experience and personal connections, etc., which was more difficult and important than acquiring explicit knowledge of family businesses.…”
Section: Knowledge Transfermentioning
confidence: 99%
“…These catalysts play a pivotal role in ensuring the seamless continuation and expansion of family businesses by facilitating the efficient conveyance of invaluable knowledge. To begin with, trust will remain a fundamental catalyst, nurturing transparent communication and cooperation, thus enabling the proficient exchange of knowledge and expertise (Huang et al ., 2023; Sirmon et al ., 2007; Szulanski, 1996). Trust also aids in establishing a feeling of security and assurance in the transfer process, guaranteeing the passage of precious knowledge devoid of hesitancy or reservation (Chirico and Salvato, 2008; Szulanski, 1996).…”
Section: Future Perspectives Over the Next 100 Years (2023–2123)mentioning
confidence: 99%
“…Similarly, culture wields a substantial influence on knowledge transfer within family businesses. The distinct culture of a family enterprise, molded by shared values, standards, and convictions, fosters an environment conducive to knowledge sharing and transfer (Chua et al ., 1999; Huang et al ., 2023; Jayantilal et al ., 2023). A robust family culture cultivates loyalty, dedication, and collective identity, prompting family members to actively engage in transferring tacit knowledge (Cabrera-Suárez et al ., 2001).…”
Section: Future Perspectives Over the Next 100 Years (2023–2123)mentioning
confidence: 99%